Pengembangan Aplikasi Augmented Reality Berbasis Android Untuk Visualisasi Struktur Sel Bakteri dan Bentuk-Bentuk Bakteri - Dimas Septiandi, Muhammad; Bima Dirgantara, Harya (KALBISCIENTIA Jurnal Sains dan Teknologi, 2019)
The purpose of this research is to develop an Augmented reality applications that was used to visualize the structure of the bacteria cell and bacteria forms in 3 dimensions. An application developed in this research were dedicated to the Android smartphone users are studying or teaching others about the bacteria cell structure and bacteria forms. Software development methods used in the research and application development is incremental. The incremental amounts required in performing this application development amounted to 4 incremental. At each incremental done the analysis, design, coding, and testing phase. 3Ds Max 2018 is used to doing the design of 3-dimensional form of the bacteria. Unity 3D version 5.6.0 f3 and Vuforia library version 6 is used to doing the development of application. The results of this research is the Android-based Augmented reality application for visualization of bacteria cell structure and bacteria forms.